2023
DOI: 10.1186/s12967-023-04518-4
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin1, not NAMPT, possesses anti-inflammatory effects in epicardial, pericardial and subcutaneous adipose tissue in patients with CHD

Trine Baur Opstad,
Bianca Papotti,
Sissel Åkra
et al.

Abstract: Background Inflammation in cardiac adipose tissue (AT) is associated with atherosclerosis. We investigated whether the epicardial-, pericardial and pre-sternal subcutaneous AT (EAT, PAT and SAT) expression of Sirtuin1 (SIRT1) and nicotinamide phosphoribosyl transferase (NAMPT) are involved in the inflammatory process in coronary heart disease (CHD), and potentially associated to nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome-related markers, macrophage polarization mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Treatment with NAMPT and NAD + improves the mitochondrial reactive oxygen species (ROS) concentration and reduces gap junction (a path of electrical propagation) activity in cardiac endothelial cells (CEC) of diabetic mice [ 41 ]. Another study revealed that the development of pulmonary arterial hypertension (PAH) in a mouse model was directly linked to nicotinamide phosphoribosyl transferase (NAMPT) [ 42 ]. In hypertrophic cardiomyopathy (HCM) a decreased level of NAMPT was observed [ 43 ].…”
Section: The Role Of Nampt In Cardiac Healthmentioning
confidence: 99%
“…Treatment with NAMPT and NAD + improves the mitochondrial reactive oxygen species (ROS) concentration and reduces gap junction (a path of electrical propagation) activity in cardiac endothelial cells (CEC) of diabetic mice [ 41 ]. Another study revealed that the development of pulmonary arterial hypertension (PAH) in a mouse model was directly linked to nicotinamide phosphoribosyl transferase (NAMPT) [ 42 ]. In hypertrophic cardiomyopathy (HCM) a decreased level of NAMPT was observed [ 43 ].…”
Section: The Role Of Nampt In Cardiac Healthmentioning
confidence: 99%